Experiences of receiving and providing maternity care during the COVID-19 pandemic in Australia: A five-cohort cross-sectional comparison - Bradfield, Zoe; Wynter, K.; Hauck, Yvonne; Vasilevski, V.; Kuliukas, Lesley; Wilson, A.N.; Szabo, R.A.; Homer, C.S.E.; Sweet, L. (PUBLIC LIBRARY SCIENCE, 2021)
Introduction The global COVID-19 pandemic has radically changed the way health care is delivered in many countries around the world. Evidence on the experience of those receiving or providing maternity care is important to guide practice through this challenging time. Methods A cross-sectional study was conducted in Australia. Five key stakeholder cohorts were included to explore and compare the experiences of those receiving or providing care during the COVID-19 pandemic. Women, their partners, midwives, medical practitioners and midwifery students who had received or provided maternity care from March 2020 onwards in Australia were recruited via social media and invited to participate in an online survey released between 13th May and 24th June 2020; a total of 3701 completed responses were received. Findings While anxiety related to COVID-19 was high among all five cohorts, there were statistically significant differences between the responses from each cohort for most survey items. Women were more likely to indicate concern about their own and family's health and safety in relation to COVID-19 whereas midwives, doctors and midwifery students were more likely to be concerned about occupational exposure to COVID-19 through working in a health setting than those receiving care through attending these environments. Midwifery students and women's partners were more likely to respond that they felt isolated because of the changes to the way care was provided. Despite concerns about care received or provided not meeting expectations, most respondents were satisfied with the quality of care provided, although midwives and midwifery students were less likely to agree. Conclusion This paper provides a unique exploration and comparison of experiences of receiving and providing maternity care during the COVID-19 pandemic in Australia. Findings are useful to support further service changes and future service redesign. New evidence provided offers unique insight into key stakeholders' experiences of the rapid changes to health services. Copyright: